Metode Flyback pada Pembangkitan Tegangan Tinggi untuk Aplikasi Plasma Electrolytic Oxidation - Kumala Mahda Habsari; Wijono; D.J. Djoko H.S. (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2017)
Flyback is one of high voltage generation methods using a low voltage source. This method has a simple circuit, which consists of two main components for generating the high voltage. In this study, flyback method is used to generate high voltage on plasma electrolytic oxidation (PEO) application. PEO is a process that combine electrochemical oxidation process and high voltage spark. This application needs high voltage to produce plasma. The plasma is used to form a new surface coating on metal. Flyback circuit is succesfully simulated on LTSpice IV. Voltage value and waveform on simulation has been observed and compared with the real one. The measured and observed part is IGB gate, output voltage of transformer before diode, and load voltage after diode. Flyback effect and waveform on simulation has the similiar result with the real one. A 10 volt input voltage can produce output voltage on the average of 1 kilovolt. Therefore, flyback simulation is able to represent flyback ability on real circuit for generating high voltage which can be used on high voltage generation for PEO application.